Blink reflex R2 changes and localisation of lesions in the lower brainstem (Wallenberg's syndrome): an electrophysiological and MRI study - Fitzek, S (BMJ Group, 1999)
OBJECTIVES—Pathways of late blink reflexes are detected by high resolution MRI. Electronically matched stroke lesions superimposed to an anatomical atlas show the suspected course. METHODS—Fifteen patients with infarction of the lower brainstem, MRI lesions and electrically elicited blink reflexes were examined. The involved structures in patients with R2 and R2c blink reflex changes were identified by biplane high resolution MRI with individual slices matched to an anatomical atlas at 10 different levels using digital postprocessing methods. RESULTS—The blink reflexes were normal in five of 15 patients (33%) and showed loss or delay of R2 and R2c to stimulation ipsilaterally to lesion (R2-i and R2c-i) in eight (53%). Loss or delay of R2-i/R2c-i was seen in lesions covering the entire trigeminal spinal tract and nucleus (TSTN) at at least one level. These infarctions were located more dorsally within the medulla. Patients with normal blink reflexes showed lesions sparing or involving the TSTN only partially. They more often had incomplete Wallenberg's syndromes and MRI lesions were located more ventrally. CONCLUSIONS—Using digital postprocessing MRI methods it was possible to identify central pathways of late blink reflex in patients with Wallenberg's syndrome. This method is suggested as a new approach to identify incompletely understood functional structures of the brainstem.